The Effectiveness of Taxation and Feed-in Tariffs - Fabio Antoniou; Roland Strausz (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study (energy) markets with dirty incumbents and costly entry by clean producers. For intermediate entry costs, the market outcome exhibits inefficient production and inefficient entry. A policy mix of three popular regulatory instruments—taxation on polluters, feed-in tariffs for clean entrants, and taxation of consumption—cannot correct these two market failures. Feed-in tariffs and consumption taxes are ineffective instruments for implementing the first best. The second best requires feed-in tariffs or consumption taxes. For a given level of production, the instruments are ineffective in influencing the overall budget, but may be effective for other budgetary concepts.
Keywords: D21; D61; H23; 330; taxation; feed-in tariffs; externalities; entry; pollution